Palestine and the palestinian local authorities: an analytical perspective - Dalloul, Mahmoud Hany M.; Ibrahim, Zuraeda Binti; Urus, Sharina Tajul (P.A. Persona e Amministrazione, 2024)
The article's objective is to provide an overview of Palestine and an analytical view of the Palestinian local government sector. The qualitative method was used by reviewing many articles, reports, books, and studies related to Palestine, in addition to the Palestinian local government sector and local authorities, using several journals and scientific search engines. Thus, the article provided a comprehensive overview of the history of the Palestinian local authorities. It also clarified the objectives of the Palestinian local authorities, in addition to their duties and characteristics. The article also worked to identify the obstacles and challenges facing the Palestinian local authorities. Moreover, it demonstrated the legal and regulatory framework governing the Palestinian local authorities. Furthermore, it presented the distribution and classification of local authorities in the southern Palestinian governorates. This article contributes to enriching the literature related to the reality of the Palestinian local authorities. Contributes to achieving a more reasonable understanding and realisation of the nature of the Palestinian local authorities. Contributes to providing a comprehensive view of the Palestinian local authorities in terms of history, purpose, tasks, characteristics, obstacles, challenges, law, and oversight.